Influence of Knee Abductor Moment on Patellofemoral Joint Stress and Self-reported Pain of Women with Patellofemoral Pain - Waiteman, Marina [UNESP] (2019)
Increased knee abductor moment (KAM) is thought to be related with elevated patellofemoral joint (PFJ) stress, a major contributor to patellofemoral pain (PFP). Knowing which parameter of the KAM relates with PFJ stress and self-reported pain is important as interventions can vary depending on the altered KAM parameter. This study aimed to compare peak, rate of moment development and impulse of KAM and PFJ stress of women with PFP and pain-free controls during stair descent; and to investigate the relationship among these variables with self-reported pain. Sixty-four women aged 18-35 years were recruited. A three-dimensional motion analysis system with link-segment models and inverse-dynamics equations was used to obtain kinetic data during a stair descent task. A previously reported algorithmic model was used to determine patellofemoral contact force (PCF) and patellofemoral contact pressure (PCP), indicatives of PFJ stress. Self-reported pain was assessed using a visual analogue scale (VAS). Women with PFP presented higher peak, rate of moment development and impulse of the KAM, PCF and PCP during stair descent than pain-free controls, suggesting women with PFP experience higher levels of PFJ stress while descending stairs. Only KAM impulse presented positive moderate correlations with self-reported pain, PCF and PCP. These findings indicate that strategies aimed at decreasing KAM impulse could reduce the load over the PFJ and improve pain of women with PFP.